Perinatal mortality among infants born during health user-fees (Cash & Carry) and the national health insurance scheme (NHIS) eras in Ghana: a cross-sectional study. Issue 1 (December 2016) - Ibrahim, Abdallah; Maya, Ernest; Donkor, Ernestina; Agyepong, Irene; Adanu, Richard
Abstract Background This research determined the rates of perinatal mortality among infants delivered under Ghana's national health insurance scheme (NHIS) compared to infants delivered under the previous "Cash and Carry" system in Northern Region, especially as the country takes stock of its progress toward meeting the Millennium Development Goals (MDG) 4 and 5. Methods The labor and maternity wards delivery records of infants delivered before and after the implementation of the NHIS in Northern Region were examined. Records of available daily deliveries during the two health systems were extracted. Fisher's exact tests of non-random association were used to examine the bivariate association between categorical independent variables and perinatal mortality. Results On average, 8% of infants delivered during the health user-fee (Cash & Carry) died compared to about 4% infant deaths during the NHIS delivery fee exemption period in Northern Region, Ghana. There were no remarkable difference in the rate of infant deaths among mothers in almost all age categories in both the Cash and Carry and the NHIS periods except in mothers age 35 years and older. Infants born to multiparous mothers were significantly more likely to die than those born to first time mothers. There were more twin deaths during the Cash and Carry system (p = 0.001) compared to the NHIS system. Deliveries by caesarean section increased from an average of 14% in the "Cash and Carry" era to an average of 20% in the NHIS era. Conclusion The overall rate of perinatal mortality declined by half (50%) in infants born during the NHIS era compared to the Cash and Carry era. However, caesarean deliveries increased during the NHIS era. These findings suggest that pregnant women in the Northern Region of Ghana were able to access the opportunity to utilize the NHIS for antenatal visits and possibly utilized skilled care at delivery at no cost or very minimal cost to them, which therefore improved Ghana's progress towards meeting the MDG 4, (reducing under-five deaths by two-thirds).